GAZİANTEP İLİ YER ADLARI ÜZERİNE BİR İNCELEME - KALKAN, GÜLŞAH PARLAK (Fırat Üniveristesi, 2014)
Yeryüzünde var olan canlı-cansız her şey, bir adla belirtilir ve kendisine verilen bu adla diğerlerinden farklılaştırılır. O halde bir ada, tanımlamaya sahip olmayan bireyin, nesnenin ya da durumun olmadığını söylemek mümkündür. Adların gramatik açıdan taşıdığı bu önemle birlikte sosyolojik bakımdan da irdelendiğinde geri planında ortak kültürel bir belleği bünyesinde barındıran sembolik göstergeler olduğu görülecektir. Her türlü varlığın, nesnenin kimliğini somutlaştıran bu göstergeler içerisinde oldukça büyük önem arz edeni ise yer adlarıdır. Yer adları, basit birer coğrafik tanımlamanın çok ötesinde; yaşanılan toprak parçasının bir millete vatan oluşunun tapu senedidir. Yaklaşık dokuz asırdır Anadolu'nun her karışını yurt tutan Türkler, bu toprakların dağına, tepesine, ovasına, yaylasına, kültürlerini ve düşünce dünyalarını şifreleyen manalı adlar vermişlerdir. Bu adların irdelenmesiyle hem bu kültür somutlaştırılabileceği gibi hem de Türk dilinin tarihi gelişimi hakkında da bilgilere ulaşmak mümkün olacaktır. Bu çalışmada, Gaziantep ili yer adlarını oluşturan yaklaşık 8.000 civarında ilçe, köy, kasaba, dere, tepe, dağ vb. yer adı, yapı, köken ve anlam bakımından incelenmiştir. Neticede Türk dilinin tarihsel gelişimi ile Türk ad verme felsefesine ait ipuçlarına ulaşılmaya çalışılmıştır. Anahtar Kelimeler: Gaziantep, ad bilimi, yer adları, su adları, dağ adları

All living and nonliving things on earth is identified by a name (noun) that makes it different from other things. Then it can be said that a person or a thing or a case that has no name has also no existence. With the importance that names carry grammatically, if it will be examined in sociological aspect, one can see the symbolic indicators that embody a common cultural memory in the background. Among these indicators that concretize identities of all kind of entities and objects the place names are of great importance. Place names are not simple geographical definitions, they are beyond it. They can be described as "title deed" of being a homeland for a nation settled in a certain piece of land. The Turks who have been settling down on every inch of Anatolia's soil for last nine centuries encoding their cultural and intellectual world gave meaningful names to mountains, hills, plains and highlands of it. The examination of the place names allows to concretize this culture on one hand and to reach a knowledge on historical development of Turkish language on the other. This dissertation focuses on the place names of Gaziantep province. The author examines about 8000 toponyms that include the names of sites as well as hydronyms, oronyms etc. within the province in terms of morphological structure, etymology and semantics. As a result the author gives some clues on the philosophy of name giving of Turks and demonstrates certain evidence of language development through local toponyms. Key Words: Gaziantep, onomastic, toponomy, oronomy, hidronomy
A study on the toponomy in Gaziantep city
Keywords: Türk Dili ve Edebiyatı